Parents' use of physical and verbal punishment: cross-sectional study in underprivileged neighborhoods - Vagner dos Santos; Paulo Henrique Dourado da Silva; Lenora Gandolfi (Elsevier, 2018)
Objective: To estimate the past-year prevalence of parental use of verbal and physical discipline in an urban sample. Method: A cross-sectional study was conducted in two underprivileged neighborhoods with nearly 80,000 inhabitants. Complex sampling was used. The households were selected by applying two-stage probabilistic sampling with stratification. A total of 401 households (sample error = 0.1) were selected by maximizing the variance (p = 0.5). The cluster sampling indicated 33 census units (sample error = 0.05). The Brazilian Portuguese version of the WorldSAFE Core Questionnaire was used to assess parental use of moderate verbal discipline, harsh verbal discipline, moderate physical discipline, and harsh physical discipline. This questionnaire asks how often mothers (respondent) and/or their husband or partner use specific disciplinary tactics. Results: The mean age of children and adolescents was 9 years (SD: 4.5). The prevalence of harsh verbal discipline was approximately 37% (28.3% [95% CI: 23.4-33.3%] for more than three times). The prevalence of harsh physical discipline was approximately 30% (21.8% [CI: 18.2-25.4%] for more than three times). Boys had higher odds of receiving harsh physical discipline [OR: 1.56, p < 0.05]. Children and adolescents with learning problems and developmental delays had higher odds of being exposed to harsh discipline than their peers without these problems. Children and adolescents with chronic health conditions (e.g., asthma) had lower odds of receiving harsh physical discipline (OR: 0.4; p < 0.05). Conclusions: Parental abuse was embedded within children and adolescents rearing practices in these two underprivileged neighborhoods. Resumo: Objetivo: Estimar a prevalência no último ano de crianças e adolescentes expostos a disciplinas físicas e verbais pelos pais e mães. Metodologia: Estudo transversal conduzido em dois bairros vulneráveis que possuem aproximadamente 80.000 habitantes. Amostragem complexa foi utilizada. As casas foram selecionadas por amostragem probabilística em duas fases. O número de 401 casas (erro amostral = 0,1) foi definido pela variância maximizada (p = 0,5). A amostragem por cluster permitiu obter o total de 33 cluster selecionados (erro amostral = 0.05). Usamos a versão brasileira do WorldSAFE Core Questionnaire para identificar disciplinas verbais moderadas, disciplinas verbais severas, disciplinas físicas moderadas e disciplinas físicas severas. O questionário pergunta a frequência que as mães (respondentes) e seus maridos/companheiros utilizaram táticas disciplinares especificas. Resultados: A média de idade das crianças e adolescentes foi de nove anos (DP: 4,5). A prevalência de disciplinas verbais severas foi de aproximadamente 37% (sendo 28,3% [95% CI: 23,4-33,3%] expostas a mais de três vezes no último ano). A prevalência disciplinas físicas severas foi de aproximadamente 30% (sendo 21,8% [CI: 18,2-25,4%] expostas mais de três vezes). Meninos tem maior chance de disciplinas físicas severas [OR: 1,56, p < 0,05]. Crianças e adolescentes com problemas de aprendizagem e atrasos no desenvolvimento apresentam maior chance quando comparado com seus pares sem problemas. Crianças e adolescentes com problema crônico de saúde tiveram chance menor de disciplinas físicas severas (OR: 0,4; p < 0,05). Conclusões: Abuso paterno e materno está contido nas práticas cotidianas de educação nestes dois bairros vulneráveis. Keywords: Child rearing, Parenting, Punishment, Poverty areas, Palavras-chave: Educação infantil, Parentalidade, Disciplina, Áreas de pobreza